THE ROLE OF COMPANY SIZE IN MODERATING RELATED PARTY TRANSACTIONS AND EARNINGS MANAGEMENT ON TAX AVOIDANCE IN MANUFACTURING COMPANIES FROM 2020 TO 2024 - Purnamasari, Puji Endah; Sartika, Farahiyah; Afifah, Nur (Proceedings of the International Conference of Islamic Economics and Business (ICONIES); Vol 11 No 1 (2025): The 11th International Conference of Islamic Economics and Business (ICONIES 2025), 2025)
This study aims to investigate the influence of Related Party Transactions (RPT) and earnings management on tax avoidance, with firm size as a moderating variable, in manufacturing companies listed on the Indonesia Stock Exchange (IDX) during 2020–2024. A quantitative descriptive approach was employed, using a sample of 26 manufacturing companies, and the data were analyzed through multiple regression and Moderated Regression Analysis (MRA). The results reveal that RPT has a positive and significant effect on tax avoidance, whereas earnings management does not exhibit a significant impact. Additionally, firm size appears to weaken the relationship between RPT and tax avoidance, though not significantly, and does not moderate the relationship between earnings management and tax avoidance. These findings indicate that tax avoidance in manufacturing companies is more strongly influenced by related party transactions than by earnings management, while firm size does not consistently act as a moderating factor.